Outcomes of intubation techniques in nasolacrimal duct blockage in adult age group: a comparative study based on Sindh, Pakistan population - Qazi, Asif Mashood; Qidwai, Nazia; Bhutto, Israr Ahmed; Penezai, Aimal Khan; Soomro, Fayaz Ahmed; Khan, Hina; Tariq, Anus (International Journal of Research in Medical Sciences, 2019)
Background: Nasolacrimal duct obstruction is listed under the heading of congenital diseases; on other hand it is also commonly present in adult age group. In population of Sindh we found these patients frequently. Through this study we revealed the surgical options for the treatment of Nasolacrimal duct obstruction in population of Sindh provenience of Pakistan. The objective of the study was to compare the outcomes of two different intubation techniques in treatment of Nasolacrimal duct obstruction between two age groups. Comparative study was conducted in the Department of Ophthalmology Al-Ibrahim Eye Hospital Karachi from May 2018 to June 2019. Methods: Total 136 numbers of patients were included on the bases of history, clinical examination and pre-operative syringing test. Non- probability convenient sampling was applied for data collection. Total 136 numbers of patients were divided into two groups on the bases of treatment and further subgroup on the bases of age ranges. Data were analyzed by SPSS version 20.0. Results: Frequency and percentage of recovery in six months in each subgroup with application of chi-square test. Frequency and percentage of post-operative complications prolong treatment and regurgitation and patency of tube in each group and subgroups. Conclusions: The results showed significant difference between the groups. Group A showed higher success rate with minimal percentage of complications and post-operative measurements in both age ranges as compare to Group B.